Religious Violence in Radicalism Content on YouTube Social Media Throughout 2023-2024 - Awang, Jellyan Alviani; Tanaem, Norma Selfi; Ibu, Akwila Priska; Hasibuan, Serepina Yoshika; Lakaoni, Judhi Kurniawan (STT Transformasi Indonesia Manado, 2025)
This study examines the phenomenon of religious-based violence in radicalism content on social media, especially the YouTube platform throughout 2023-2024. This article uses qualitative research with a library approach as a data collection technique that will analyze YouTube content related to religious violence in radicalism content and is supported by reference sources, namely journals, books, Google Scholar, and Semantic Scholar. The rise of content with extreme religious narratives raises concerns about the potential for conflict and social polarization. Through in-depth analysis, this study found that religion should be understood as a social system that contains collective values, where the concept of the Kingdom of God is the basis that emphasizes love and peace. This serves to distinguish between true religious teachings and deviant interpretations that can be used to justify violence. This finding also underlines the importance of viewing religion as a tool for peace that can encourage dialogue and mutual understanding between religious communities, not as a source of violence or conflict. This study emphasizes that implementing a comprehensive understanding of religion in modern public spaces, such as social media, is an important step to reduce the spread of radicalism. It is hoped that this effort can build collective awareness of the importance of prioritizing universal and peaceful religious values, so that society can work together to create a public space that is safe, harmonious, and free from the threat of religious-based violence.